2013
DOI: 10.1017/s0950268813000678
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in cryptosporidiosis associated with introduction of enhanced filtration of drinking water at Loch Katrine, Scotland

Abstract: Previous evidence has suggested an association between cryptosporidiosis and consumption of unfiltered drinking water from Loch Katrine in Scotland. Before September 2007, the water was only micro-strained and chlorinated; however, since that time, coagulation and rapid gravity filtration have been installed. In order to determine risk factors associated with cryptosporidiosis, including drinking water, we analysed data on microbiologically confirmed cases of cryptosporidiosis from 2004 to 2010. We identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…A large outbreak of cryptosporidiosis that occurred in Scotland in 2000 was associated with drinking water supplied from Loch Katrine and the catchment area surrounding the loch had a large sheep and cattle population. Livestock were removed from the area by the water authorities as a precaution and a rapid gravity filtration system was introduced, which successfully reduced the Cryptosporidium oocysts from the finished water [62]. An important example of health authorities working together with farmers to help protect water catchments is one of the largest water supply systems in the USA, providing over 9 million people in the New York City area with 4.5 billion litres daily from a single source of unfiltered water.…”
Section: Protecting Water Catchments From Contaminated Livestock Faecesmentioning
confidence: 99%
“…A large outbreak of cryptosporidiosis that occurred in Scotland in 2000 was associated with drinking water supplied from Loch Katrine and the catchment area surrounding the loch had a large sheep and cattle population. Livestock were removed from the area by the water authorities as a precaution and a rapid gravity filtration system was introduced, which successfully reduced the Cryptosporidium oocysts from the finished water [62]. An important example of health authorities working together with farmers to help protect water catchments is one of the largest water supply systems in the USA, providing over 9 million people in the New York City area with 4.5 billion litres daily from a single source of unfiltered water.…”
Section: Protecting Water Catchments From Contaminated Livestock Faecesmentioning
confidence: 99%
“…Only one study from Scotland reported on the use of enhanced filtration of drinking water as an intervention for cryptosporidiosis, where the incidence of cryptosporidiosis was associated with unfiltered water supply to homes (OR 1.86) [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our included papers investigated water exposures most frequently despite evidence that in industrialised countries in recent years, drinking treated mains water is unlikely to cause a significant amount of sporadic cryptosporidiosis (94,95). However, despite improved legislation for drinking water quality (80) deficiencies can persist and it is important to keep monitoring this pathway (96,97).…”
Section: Discussionmentioning
confidence: 99%